Learnings from Rolls‐Royce hybrid propulsion systems in flight testing of High Power, High Scalability Hybrid Powertrain aircraft - Péter Bodolai; Attila Vörösváczki; Gábor Bihari; Szabolcs Fási; Péter Szabó; Zoltán Koltai (IET Electrical Systems in Transportation)
Abstract This article describes the collaborative efforts between Tecnam, Rolls‐Royce, and Rotax to equip a 4‐seat Tecnam P2010 aircraft with a parallel hybrid‐electric powertrain, the first of its kind ever developed for general aviation, to help reduce fuel consumption while maintaining, and even extending, the aircraft range. The High Power, High Scalability Hybrid Powertrain project set out to design, build, ground‐test and demonstrate in a flight campaign such a propulsion system. Creating a parallel hybrid‐electric drive system, which brings together the electric and combustion engine worlds, creates a completely new set of challenges in the design, assembly, operation, and safety assurance of aircraft which must be addressed for a successful business proposition. The article reflects on some of the challenges faced as this innovative and scalable powertrain was developed on the road to minimise emissions in the aviation industry.